Psychological pressures and their relationship to the competitive orientation of football players in the Iraqi Premier League for the 2018-2019 season - Thare Hani, Ahmad; Saad Abdulhameed, Ali; Mohammed Ali Qasim, Amwag (International Journal of Psychosocial Rehabilitation, 2020)
The psychological state of the athlete affects a great extent on the level of performance negatively or positively, especially that all teams share the same ambition in the competition and get championships, which provokes them different emotions, and the higher the degree of competition, the psychological pressures increase their different dimensions and forms and affected The motivation of achievement in the players, therefore, must be identified the sources of these pressures in the players and try to work to face them and pay attention to the guidance and psychological guidance of the players to alleviate these psychological pressures, as football players in the Iraqi premier league are subjected to multiple psychological pressures resulting from the performance matches and intense competition within the green rectangle. So the player needs to be prepared psychologically, which leads to increased readiness for the next response and self-confidence and focus on positive aspects that help to achieve the best achievement. The importance of research lies in highlighting the pressures The psychological orientation and the extent of the relationship between them in the Iraqi Premier League football players, and the problem is purely that the players of the university team are exposed to a range of pressures, especially when it requires them to exert a lot of physical, mental and psychological effort and requires them at the same time Competition and achieving the best achievement, the study aims to identify the level of psychological pressures, competitive orientation and relationship between them for football players in the Iraqi Premier League for the 2018-2019 season.